Pengaruh Kredibilitas Sosial Media Influencer Akun TikTok @dosenskincare Terhadap Pemenuhan Kebutuhan Informasi Perawatan Kulit Wajah Pada Followers - Weni Adityasning Arindawati; Maulani, Anita; Yanti Tayo (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The increasing interest and awareness of Indonesian society about skincare issues drives the fulfilment of the need for right information about it. Along with this, social media influencer is one of the important communicators who fulfill the need for information about facial skincare. This study aims to find out the influence of social media influencers on tiktok @dosenskincare accounts on fulfilling facial skin care information needs based on source credibility theory. This research used quantitative methods. The data source was collected through a survey with a sample of 400 followers of the @dosenskincare tiktok account. Data analysis used simple regression with the assistance of SPSS software. The results showed that the credibility of social media influencers of the tiktok @dosenskincare account influenced the fulfilment of facial skin care information needs. This study confirms that social media influencer is an important communicator in the digital era who is a reference for information about skin care.